2011
DOI: 10.2340/00015555-1031
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Stress and Coping in Alopecia Areata: A Questionnaire Survey and Qualitative Study Among 45 Patients

Abstract: The controversial role of psychosocial stress in alopecia areata has been discussed widely, but there has been little research into patients' subjective stress experiences and coping. The aim of this study was to explore general and specific coping strategies in alopecia areata and to assess the role of psychosocial stress in the onset and course of alopecia areata from the patient's viewpoint. Forty-five patients conducted measurements of general coping strategies and body image. Qualitative data analysis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 20 publications
5
54
0
3
Order By: Relevance
“…Some studies reported a clear prevalence of psychiatric co morbidity and personality traits in alopecia areata, particularly anxiety and depression, while others conclude that they are less important [39]. However, a questionnaire survey and qualitative study among 45 patients found that stress seems to play a role in the onset and aggravation of alopecia areata and the disorder has its impact on health-related QoL [40,41] .…”
Section: Alopecia Areatamentioning
confidence: 96%
“…Some studies reported a clear prevalence of psychiatric co morbidity and personality traits in alopecia areata, particularly anxiety and depression, while others conclude that they are less important [39]. However, a questionnaire survey and qualitative study among 45 patients found that stress seems to play a role in the onset and aggravation of alopecia areata and the disorder has its impact on health-related QoL [40,41] .…”
Section: Alopecia Areatamentioning
confidence: 96%
“…A recent genome-wide association study has shown an association with genomic regions containing genes controlling both innate and acquired immunity [1]. AA has a dramatic impact on quality of life [2] and affects several aspects of the patients’ life [3]. Treatment of disfiguring AA is one of the most challenging goals in dermatology, and there is no consensus for active management because of a lack of treatment options of demonstrated efficacy and limited evidence from good-quality randomized, double-bind, placebo-controlled trials [4].…”
Section: Introductionmentioning
confidence: 99%
“…6 Psychosocial stress may also play a role in alopecia areata, although this claim remains controversial. 7 Recently, a questionnaire survey and qualitative study of 45 patients concluded that "…psychological interventions in alopecia areata should focus on the training of general and alopecia areata-specific coping competences and techniques of regulating emotionality". 7 Hence, although the temporal association of alopecia areata in the present patient was consistent with a drug-induced etiology, psychosocial stress may also be a contributory factor in the new onset of alopecia areata in oncology patients.…”
Section: Discussionmentioning
confidence: 99%